1998
DOI: 10.2105/ajph.88.11.1630
|View full text |Cite
|
Sign up to set email alerts
|

Return to work following injury: the role of economic, social, and job-related factors.

Abstract: Injury is well recognized as a leading contributor to work disability. Estimates of the economic costs associated with lost work days following injuries occurring in a single year exceed $95 billion (1995 dollars

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
215
7
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(240 citation statements)
references
References 43 publications
13
215
7
5
Order By: Relevance
“…With regard to work environment exposures, the present finding of ERP being more prevalent when exposed to extreme bending/twisting of neck/back, or working mainly standing/squatting suggests an overlap between determinants of ERP and permanent work disability retirement: several studies point out heavy manual labour (Borg and Burr 1997;Krause et al 1997Krause et al , 2001Andersson et al 1983;Danchin et al 1982;Dasinger et al 2000;Høgelund 2000;Lanier and Stockton 1998;Mackenzie et al 1998;Rønnevik 1988) , repetitive or continuous strain, musculoskeletal strain, uncomfortable working position, and crouching, (Krause et al 1997) and bending, twisting or working in fixed positions (Bergquist-Ullman and Larsson 1977) as determinants of retirement due to work disability. This overlap could reflect that ERP is used as an exit option before physical work strain develops into work disability.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…With regard to work environment exposures, the present finding of ERP being more prevalent when exposed to extreme bending/twisting of neck/back, or working mainly standing/squatting suggests an overlap between determinants of ERP and permanent work disability retirement: several studies point out heavy manual labour (Borg and Burr 1997;Krause et al 1997Krause et al , 2001Andersson et al 1983;Danchin et al 1982;Dasinger et al 2000;Høgelund 2000;Lanier and Stockton 1998;Mackenzie et al 1998;Rønnevik 1988) , repetitive or continuous strain, musculoskeletal strain, uncomfortable working position, and crouching, (Krause et al 1997) and bending, twisting or working in fixed positions (Bergquist-Ullman and Larsson 1977) as determinants of retirement due to work disability. This overlap could reflect that ERP is used as an exit option before physical work strain develops into work disability.…”
Section: Discussionmentioning
confidence: 77%
“…Job dissatisfaction has been found to be positively associated with work disability in some studies (Krause et al 1997;BergquistUllman and Larsson 1977), but not in others (Krause et al 2001;Mackenzie et al 1998). Low job seniority is consistently associated with longer duration of work disability also after controlling for age (Dasinger et al 2000;Krause et al 2001;Johnson and Ondrich 1990).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As return-to-work is influenced by a number factors, it is possible that these factors may make a more significant contribution to return-to-work decisions and outcomes than line manager behaviours. For example, we did not measure individual factors that influence return to work such as health beliefs [40], clinical factors such as advice from healthcare professionals [40] and contextual factors such as family role [41]. The contribution of these factors to return to work in conjunction with line manager behaviours need to be further explored.…”
Section: Concurrent Validitymentioning
confidence: 99%
“…Previous research has consistently demonstrated that major trauma results in significant functional limitations and has a negative impact on mental health [18,22,26].…”
Section: Introductionmentioning
confidence: 99%